1998
DOI: 10.1002/(sici)1096-9136(199808)15:8<683::aid-dia643>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Does chronic smoking influence fibrinolytic potential in Type 1 diabetes mellitus?

Abstract: Tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor (PAI-1) were studied in 18 smokers and 18 closely matched non-smokers, all of whom had Type 1 diabetes mellitus (DM). None of the patients had advanced complications of diabetes. The t-PA and PAI-1 antigen levels were measured in plasma before and after venous occlusion, and were normal in Type 1 diabetes regardless of smoking status. Platelet PAI-1 levels were also measured and were found to be normal both in smokers and non-smokers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…reported that the fibrinolytic defence system is impaired in many patients with Type 1 and Type 2 diabetes irrespective of age or diabetes duration [15]. Though all the mechanism whereby PAI‐1 changes in diabetes might produce a hypofibrinolytic state are not clear, it should be recognized that several well‐established cardiovascular risk factors such as smoking [16,17], hypertriglyceridaemia [3,17] and obesity [18] are also associated with a decreased fibrinolytic activity. Of particular relevance to the current analyses is the correlation with triglycerides, which was the major independent multivariate predictor of CAD, and that with HbA 1 , the major predictor of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the fibrinolytic defence system is impaired in many patients with Type 1 and Type 2 diabetes irrespective of age or diabetes duration [15]. Though all the mechanism whereby PAI‐1 changes in diabetes might produce a hypofibrinolytic state are not clear, it should be recognized that several well‐established cardiovascular risk factors such as smoking [16,17], hypertriglyceridaemia [3,17] and obesity [18] are also associated with a decreased fibrinolytic activity. Of particular relevance to the current analyses is the correlation with triglycerides, which was the major independent multivariate predictor of CAD, and that with HbA 1 , the major predictor of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that higher plasma levels of fibrinogen and viscosity are the main contributors to higher coagulability found in smokers, whereas the lower fibrinolytic potential is mainly attributed to an increase in PAI-1 activity and possibly also a decrease in tPA activity and lower plasminogen levels. 107,228,229,244…”
Section: Smokingmentioning
confidence: 99%
“…It is possible that smoking affects especially the response of insulin to glucose, and not so much the basic insulin levels. Similarly, the finding of lower tPA-ag in female smokers seems surprising, since no association between smoking and tPA-ag is found in other studies (38,39). However the number of women in these studies was limited, and no extended data on tPA-ag and smoking for women in particular are available.…”
Section: Discussionmentioning
confidence: 88%